Performance analysis of AODV and AOMDV over SMAC and IEEE 802.15.4 in Wireless Multimedia Sensor Network - Ben Ammar, Amira; Bouattay, Olfa; Dziri, Ali; Terre, Michel; Youssef, Habib (International Wireless Communications and Mobile Computing Conference (Online), 2015)
Wireless Multimedia Sensor Networks (WMSNs) have recently gained a great attention of the research community as potential solutions for wide range of applications. However, they are subject to strict constraints due to their limited energy, limited processing capacities in contrast to the huge video data rate to be transmitted. To tackle with this challenge, we investigate in this paper, various protocols dedicated to the WMSNs in each layer aiming to reduce the amount of video data using powerful video encoder or/and reduce the energy consumption by increasing the life cycle of each node and consequently the life cycle of the whole network. Specifically, we consider the protocols of the application, network, and MAC layers. We have used the NS-2 framework, in which we have added the H264 encoder and decoder as application layer protocol. We have used the IEEE 802.15.4 and the SMAC protocols for the MAC layer, and the AODV and the AOMDV for the network layer. The obtained results are evaluated by the dead nodes number, the energy consumption and the Peak Signal to Noise Ratio (PSNR) for the video decoding quality.